Associations between cortisol stress responses and limbic volume and thickness in young adults: an exploratory study - Henze, G-I; Konzok, J; Kudielka, BM; Wüst, S; Nichols, TE; Kreuzpointner, L (Wiley, 2023)
The investigation of the relationship between neural measures of limbic structures and hypothalamic pituitary adrenal axis responses to acute stress exposure in healthy young adults has so far focused in particular on task-based and resting state functional connectivity studies. Thus, the present study examined the association between limbic volume and thickness measures and acute cortisol responses to the psychosocial stress paradigm ScanSTRESS. Using Permutation Analysis of Linear Models controlling for sex, age, and total brain volume, the associations between (sex-specific) cortisol increases and human connectome project style anatomical variables of limbic structures (i.e., volume and thickness) were investigated in 66 healthy and young (18-33 years) subjects (35 men, 31 women taking oral contraceptives). In addition, exploratory (sex-specific) bivariate correlations between cortisol increases and structural measures were conducted. The present data provide interesting new insights into the involvement of striato-limbic structures in psychosocial stress processing, suggesting that acute cortisol stress responses are also associated with mere structural measures of the human brain. Thus, our pre-liminary findings suggest that not only situation- and contextdependent reactions of the limbic system (i.e., blood oxygenation level dependent reactions) are related to acute (sex-specific) cortisol stress responses, but also basal and somewhat more constant structural measures. Our study hereby paves the way for further analyses in this context and highlights the relevance of the topic.